Nhận thức của sinh viên ngành Ngôn ngữ Anh về khả năng có việc làm và định hướng nghề nghiệp - Phương Thị Duyên, Phương Thị Duyên; Trần Minh Trang, Trần Minh Trang; Nguyễn Việt Hằng, Nguyễn Việt Hằng; Phạm Lệ Vân, Phạm Lệ Vân; Nguyễn Thị Ánh, Nguyễn Thị Ánh (Tạp chí Giáo dục, 2026)
The pressing need for Vietnamese higher education institutions is to align training with labor market demands, as mandated by the Law on Higher Education and government directives. Enhancing students’ awareness of employability is identified as a crucial step toward this goal. Using a quantitative research approach, the study investigates English language students’ perceptions of employability and career orientation. Findings reveal that while students generally recognize employability, their evaluations vary across factors and increase with academic progression. Moreover, employability awareness is consistently higher than engagement in career orientation activities. These insights provide valuable implications for curriculum enhancement and career counseling in higher education.